MODEL NETWORKING SEKOLAH SEBAGAI BASIS PENINGKATAN KUALITAS PENDIDIKAN DI SEKOLAH MENENGAH KEJURUAN - Suhartanta Suhartanta (Jurnal Kependidikan, 2011)
The objective of this study is to find out a networking model between vocational schools and the best matching stakeholders. The study is conducted in vocational schools in the province of Yogyakarta covering a range of three years. The study is research development in design. Data sources are parties from the world of work, school principles, and vocational school development team. Data collection is conducted through observation, interviews, and documentation. Data analysis is descriptive. Research findings show: (1) The networking model developed in the study is effective for obtaining data and information about the needs of the work fields; and (2) Schools have been able to translate data and information acquired from the fields in the form of operational activities including the persons in charge. When schools are able to further develop this ability to other sources of data and information, it is expected that the schools will be more responsive towards the growth and advancement of the needs of the work fields. Therefore, quality and relevance problems of graduates can be solved